Pertanggungjawaban Direksi Atas Perbuatan Melawan Hukum Berupa Penyatuan Harta dalam Kepailitan Perseroan - Tabitha Fransisca Romauli Nababan; Ema Nurkhaerani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the liability of directors for unlawful acts in the form of merging personal assets with corporate assets in the context of bankruptcy of limited liability companies. Although the principle of separation of assets protects the personal assets of directors, there are conditions in which this principle can be revealed through the principle of piercing the corporate veil. The merging of personal assets by directors, which causes losses or bankruptcy of the company, can be held accountable. The Limited Liability Company Law and the Civil Code emphasize that if proven to have committed unlawful acts or negligence in carrying out their duties, directors can be sued in civil court and their assets confiscated as part of the bankruptcy estate. This study applies a normative legal approach and a literature study method to analyze legal norms and the liability of directors for losses due to bankruptcy. The aim is to provide an understanding of the legal liability mechanism for directors who abuse their authority in managing corporate assets. By applying the principle of justice, directors can be held personally responsible for the protection of creditors and fair law enforcement.